Modelling of rainfall: A measurable tool in sustainable agriculture - Thushyanthy, T. (Journal of Environmental Monitoring and Restoration, 2007)
The study revel that summarizing large volume of rainfall data as concisely as possible without discarding the important information such as start, end and length of the rainy season, the distribution of rainfall amounts and the risks of dry spells throughout the year using gamma distribution and fiducial probability. The models fitted with gamma distribution and fiducial probability can be used successfully for the purpose of assisting sustainable agriculture with incident rainfall, for adopting suitable crops and cultivars for defining cropping calendar and to predict crop failure
Keywords: Rain Fall; Drought; Gamma Distribution Function; Fiducial Probability